Ictal kissing behavior: Neurological and psychodynamic overview - KILIÇ, ÖZGE; TAŞKIRAN, Emine; Ozmen, Mine; Kilic, ÖZGE; Senturk, Asli; ÖZKARA, Çiğdem (My University, 2013)
This study is based on the psychodynamic and neurological analysis of three Turkish patients who displayed ictal kissing automatism during their seizures. To unveil the probable underlying causes of their kissing behaviors, all patients underwent psychiatric interviews after being evaluated by ictal video-EEG recordings. The group consisted of two females (ages 35 and 29) and one male (age 26). In addition to prominent oral automatisms, each patient also displayed behaviors of kissing or blowing kisses to individuals at close proximity. Seizures were related to the right temporal lobe in two patients and the left temporal lobe in one patient. Magnetic resonance imaging showed mesial temporal sclerosis in two of the patients (one left, one right) and was normal in one. According to the DSM-IV-TR criteria, each of the three patients also suffered from major depression, while the psychodynamic interviews revealed traumatic childhood histories and intense unfulfilled affective needs. (C) 2013 Elsevier Inc. All rights reserved.